Evaluation of Control Link Impacts on the IRS Assisted Communication System with Hardware-in-the-Loop Simulation - Zeng, Xianshi; Bühlmeyer, Jonas; Weigel, Robert; Irnstorfer, Florian (2024 15th German Microwave Conference (GeMiC), 2024)
With the development of Intelligent Reflecting Surface (IRS) technology, the network performance of the control channel has an increasing impact on IRS systems. This paper presents a hardware-in-the-loop (HiL) simulation methodology for the IRS controller using real network devices. We demonstrate the behaviour of a control channel connected to the simulated IRS-based communication platform. This provides test results that correlate with wired and wireless network connection. In addition, previous work has investigated the mobile user tracking (UT) scheme and proposed methods to achieve a higher signal-to-noise ratio (SNR) in the downlink case, which will provide a theoretical upper bound. Our experimental results are analysed and compared with previous simulation methods. The results show that the proposed HiL simulation methodology can validate the functionality of the UT scheme and emphasise the importance of considering the impact of the non-ideal control link on the IRS system.<br

PMSE-xG – 5G for Programme Making and Special Events - Bühlmeyer, Jonas; Hertlein, Markus; Fischer, Georg (2nd International Conference on Signals and Systems 2018 (ICSigSys 2018), 2018)
This paper provides a short overview over the prerequisites for the use of 5G for Programme Making and Special Event (PMSE). These will be shortly discussed in the context of the current development of 5G and the German research and development (R&D) project PSMExG. In the project PMSE-xG different use cases of PMSE were examined and demonstration models will be created. This paper focuses on the use of 5G for broadband, low latency and ultra-reliable video streaming in production scenarios like motion picture or television studios. For a first attempt 4G+ software defined radio (SDR) solutions are used to measure the critical parameters and to emphasize the important aspects. After the abstract some general information about the project will be given and the project is further introduced. Subsequently the project partners shall be introduced. Then the different use cases will be presented in short. Afterwards the high data rate streaming will be discussed in focus. Some measurements with two different Software Defined Radio (SDR) platforms are presented then. These results will be discussed before the result will be summariz
Keywords: PMSE-xG; PMSE; 5G; LTE; 4G; SDR; USRP; MIMO; Networking; Communications

PMSE-xG –Wireless Communication in Mobile Networks for Programme Making and Special Events - Hertlein, Markus; Bühlmeyer, Jonas; Elhaddad, Ahmed; Fischer, Georg (2nd International Conference on Signals and Systems 2018 (ICSigSys 2018), 2018)
This paper provides a short overview of the German research and development (R&D) project PMSE-xG, which aims to create the prerequisites for using the next mobile standard for broad-band low-latency ultra-reliable connections (5G) especially for Programme Making and Special Events (PMSE). The PMSE manufacturers have so far focused on highly specialized, link-based solutions. This strategy was undermined by the fact that more and more spectrum is assigned to mobile communication systems like Long Term Evolution (LTE). Therefore, both technologies are competing for the rare spectrum. Working with the current standard for wireless communication Long Term Evolution (LTE), the PMSE-xG project is a first feasibility study to integrate PMSE applications into a mobile communication standard and aims to integrate these different use cases of PMSE through future projects into 5G. Through the interaction and cooperation with different stakeholders from industry, research, standardization, regulation and users, PMSE-xG tries to achieve this. Furthermore, it will lay the foundations for other vertical industries in 5G and for further cooperation with them. Furthermore, the video demonstrator is introduced in this paper. Still some work has to be done but the goals of the project are reachabl
Keywords: PMSE; SDR; LTE; 5G; low-latency; broad-band; ultra-reliable wireless communication

Time Synchronization of Spatial Separated Areas for AV-Production - Bruckmeyer, Heiko; Bühlmeyer, Jonas; Ackermann, Thomas; Fischer, Georg (2021 Joint Conference of the European Frequency and Time Forum and IEEE International Frequency Control Symposium (EFTF/IFCS), 2021)